Financial development and economic growth nexus: A rejoinder to Tsionas. (4th April 2019) - Nyasha, Sheilla; Odhiambo, Nicholas Mbaya
Abstract: Tsionas has offered a more revisionist approach to the empirics of the nexus between financial development and economic growth following our paper entitled 'Financial development and economic growth nexus: A revisionist approach'. In the current note, we engage Tsionas' approach in tandem with our original finance–growth nexus review. We concur with Tsionas' approach and reiterate that the debate on the relationship between financial development and economic growth remains a complex terrain both on the theoretical and empirical fronts.